Competitiveness through agricultural export performance experience from Indonesia and Thailand - Abdul Rahim, Joehansyarief (2003)
Competitiveness can be measured into four main conditions that incorporate both internal and external factors need to be present to allow country compete successfully. These include (i) factor conditions, such as the availability of skilled labor and infrastructure;(ii) demand conditions for the products of the industry; (iii) related and supporting industries including competitive suppliers; and (iv) firm strategy, structure, and rivalry. Together these four factors create the context in which country in an industry are born and compete. Competitiveness of a nation in less developed countries, especially like Indonesia and Thailand can much be easier calculated from the performance of the industry, which is likely, an agricultural supply and demand performance. In the 1960s, the agricultural export performance was similar between two Southeast Asia countries (Indonesia and Thailand), both in nominal and real value term. Those two countries were selected despite other ASEAN countries because of the performance in the past four decades where both nation were able to diversified and adjust their agricultural product not only for local consumption, but also include the export performance. One important factor resulting in the differences is the ability of diversification and adjustment of agricultural exports when the market conditions changed. The differences in export performance between the two countries are characterized clearly in contribution of each factor to explain the export growth rate. Among the factors contributing to the export growth rate for principal agricultural products, commodity diversification plays a significant role in Indonesia compared with Thailand. Agricultural exports are often considered less promising because of the inelastic demand for agricultural products to both price and income. However, at the level of trade flows by commodity and by market, there are a lot of opportunities to gain from exports. Whether agricultural exports can remain to contribute to economic growth and rural welfare improvement depends on the ability to adjust to agricultural structure to the changes in relative resource scarcity and comparative advantage in the course of economic development.